Evaluation of the sensitivity on mesoscale eddy associated with the sea surface height anomaly forecasting in the Kuroshio Extension - Jiang, Lin; Duan, Wansuo; Wang, Hui; Liu, Hailong; Tao, Lingjiang (Frontiers in Marine Science, 2023)
The sensitivity of the sea surface height anomaly (SSHA) forecasting on the accuracy of mesoscale eddies over the Kuroshio Extension region, which was determined by the Conditional Nonlinear Optimal Perturbation (CNOP) method using a two-layer quasi-geostrophic model, is evaluated by adopting multiply realistic marine data sets through an advanced particle filter assimilation method. It is shown that, if additional observations are preferentially assimilated to the sensitive area on mesoscale eddies identified by the CNOP, where the eddies present a clear high-to low-velocity gradient along the eddy rotation, the forecast skill of the SSHA can be much significantly improved. It is also demonstrated that the forecasts of the SSHA in the region where the large scale mean flow possesses much stronger barotropic or/and baroclinic instability tend to exhibit stronger sensitivity to the accuracy of the initial field in the sensitive area of the mesoscale eddies. Therefore, more attentions should be preferentially paid to the assimilation of the additional observations of the mesoscale eddies for the SSHA forecast in the region with strong velocity shear of ocean circulation. The present study verifies the sensitivity on mesoscale eddies of SSHA forecasts derived by the two-layer quasi-geostrophic model using multiply sets of realistic oceanic data, especially including observation and reanalysis data, which further additionally demonstrates the importance of targeted observations of mesoscale eddies to the SSHA forecast in the regions of strong velocity shear of ocean circulation and provides more credible scientific basis for the field campaign of the targeted observations for mesoscale eddies associated with the SSHA forecasting.